Comparison of Regenerative Tissue Quality following Matrix-Associated Cell Implantation Using Amplified Chondrocytes Compared to Synovium-Derived Stem Cells in a Rabbit Model for Cartilage Lesions - Hagen Schmal; Justyna M. Kowal; Moustapha Kassem; Michael Seidenstuecker; Anke Bernstein; Katharina Böttiger; Tanshiyue Xiong; Norbert P. Südkamp; Eva J. Kubosch (Hindawi Limited, 2018)
Known problems of the autologous chondrocyte implantation motivate the search for cellular alternatives. The aim of the study was to test the potential of synovium-derived stem cells (SMSC) to regenerate cartilage using a matrix-associated implantation. In an osteochondral defect model of the medial femoral condyle in a rabbit, a collagen membrane was seeded with either culture-expanded allogenic chondrocytes or SMSC and then transplanted into the lesion. A tailored piece synovium served as a control. Rabbit SMSC formed typical cartilage in vitro. Macroscopic evaluation of defect healing and the thickness of the regenerated tissue did not reveal a significant difference between the intervention groups. However, instantaneous and shear modulus, reflecting the biomechanical strength of the repair tissue, was superior in the implantation group using allogenic chondrocytes (p<0.05). This correlated with a more chondrogenic structure and higher proteoglycan expression, resulting in a lower OARSI score (p<0.05). The repair tissue of all groups expressed comparable amounts of the collagen types I, II, and X. Cartilage regeneration following matrix-associated implantation using allogenic undifferentiated synovium-derived stem cells in a defect model in rabbits showed similar macroscopic results and collagen composition compared to amplified chondrocytes; however, biomechanical characteristics and histological scoring were inferior.